Action 3:30R: process evaluation of a cluster randomised feasibility study of a revised teaching assistant-led extracurricular physical activity intervention for 8 to 10 year olds - Byron Tibbitts; Alice Porter; Simon J. Sebire; Emma L. Bird; Emily Sanderson; Chris Metcalfe; Jane E. Powell; Russell Jago (BMC, 2019)
Abstract Background Numerous interventions to increase children's physical activity levels are published, yet, few studies report indicators of external validity. Process evaluations are critical for assessing intervention implementation, sustainability and effectiveness. A mixed-methods process evaluation, using the RE-AIM framework, was conducted to evaluate the internal and external validity of Action 3:30R, a revised teaching assistant-led after-school intervention which aimed to increase physical activity in children aged 8-10 years and was underpinned by Self-determination Theory (SDT). Methods Data were collected and reported in line with the five components of RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance). Quantitative measures included logbooks, registers and self-reported teaching-efficacy, autonomy support, child enjoyment and perceived exertion questionnaires. Questionnaire data were collected at three points throughout the 15-week intervention. Observations by trained researchers were also conducted to assess fidelity to the intervention manual and its underpinning theory. Post-intervention focus groups with pupils and interviews with teaching assistants (TAs), school staff and external stakeholders explored the implementation and potential sustainability of Action 3:30R from stakeholders' perspectives. Results Action 3:30R appealed to a broad range of pupils, including girls and less-active pupils. The Action 3:30R TA training was implemented as intended and was perceived as valuable professional development. Releasing staff for training was a barrier in two of the six intervention schools, which were unable to deliver the intervention as a result. Pupils enjoyed the intervention, and the Action 3:30R core principles underpinned by SDT were implemented with high fidelity, as was the intervention itself. Scheduling conflicts with other clubs and lack of parental support were perceived as the main barriers to recruitment and attendance. Lack of space and season were cited as the main barriers affecting the quality of delivery. The study shows evidence of maintenance, as one intervention school decided to continue Action 3:30R beyond the study. Funding and continued TA training were suggested as factors which may affect the maintenance of Action 3:30R. Conclusions Action 3:30R is an enjoyable, autonomy-supportive after-school programme, which engages a range of pupils and offers TAs valuable training. RE-AIM provided helpful structure and is recommended for intervention evaluations. Trial registration ISRCTN34001941. Prospectively registered 01/12/2016.